Friction and wear behaviors of a high nitrogen austenitic stainless steel Fe-19Cr-15Mn-0.66N - Qiao, Yanxin; Sheng, Shaolong; Zhang, Lianmin; Chen, Jian; Yang, Lanlan; Zhou, Huiling; Wang, Yuxin; Zheng, Zhibin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The friction and wear behaviors of a Fe-19Cr-15Mn-0.66N high nitrogen austenitic stainless steel (HNSS) were investigated. Tribology experiments were carried out under different applied loads of 5 N, 10 N, 15 N and 20 N. Scanning electron microscope (SEM) and laser scanning confocal microscope (LSCM) were used to explore the wear mechanisms under different loads and the reasons for the improved wear resistance. The lower friction coefficient and improved wear-resistant properties were observed with the increase of applied loads. Under a higher load, the friction process enhanced the ability of work hardening, which improved its surface hardness and thus the increased wear resistance of HNSS.
Keywords: high nitrogen austenite stainless steel; wear; work hardening; friction coefficient